Serum procalcitonin levels in prostate cancer: A new biomarker?. Issue 2 (May 2018) - Canat, Lütfi; Atalay, Hasan A; Can, Osman; Alkan, İlter; Ötünçtemur, Alper
Background: To examine the role of serum procalcitonin as a biomarker for the detection of prostate cancer in patients with a serum prostate-specific antigen less than 20.0 ng/mL. Methods: The prospective study included patients with a prostate-specific antigen level of 2–20 ng/mL, who underwent prostate biopsy. Clinical and pathological data such as age, prostate volume, prostate-specific antigen, procalcitonin, and Gleason score were reviewed. All patients were divided into three groups with total prostate-specific antigen level between 2 and 4 ng/mL, 4.1 and 10 ng/mL, and 10.1 and 20 ng/mL. Results: Of 227 patients who underwent biopsy, prostate cancer was diagnosed in 74 (32.6%) patients and the remaining 153 patients had a benign condition. The difference in mean serum procalcitonin values was significantly higher in the prostate cancer compared with the benign group (0.06 ± 0.03 vs 0.04 ± 0.03 ng/mL; p  = 0.0001). Using a threshold of 0.045 ng/mL, procalcitonin was 54.1% sensitive and 80.3% specific (area under curve = 0.683). Serum procalcitonin levels were not able to differentiate between prostate cancer patients with prostate-specific antigen level of 2–4, 4.1–10, and 10.1–20 ng/mL. Conclusion: Based on this prospective study, procalcitonin can be a novel supplementary biomarker to increase the accuracy of prostate cancer screening.